2021
DOI: 10.3390/cancers13123045
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Transcriptomic Analysis of Non-Tumorigenic Tissues Reveals Aging-Related Prognostic Markers and Drug Targets in Renal Cell Carcinoma

Abstract: The relationship between expression of aging-related genes in normal tissues and cancer patient survival has not been assessed. We developed a genome-wide transcriptomic analysis approach for normal tissues adjacent to the tumor to identify aging-related transcripts associated with survival outcome, and applied it to 12 cancer types. As a result, five aging-related genes (DUSP22, MAPK14, MAPKAPK3, STAT1, and VCP) in normal tissues were found to be significantly associated with a worse survival outcome in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Through statistical analyses, Soh et al [ 34 ] identified cancer-related miRNAs associated with somatic copy number alterations and validated them in vitro by measuring the viability and proliferation rates of cells transfected with their inhibitors. Oh et al [ 35 ] identified aging-related genes in the kidney tissue using a regression method and validated them in vivo using mouse and zebrafish models. Joehanes et al [ 36 ] selected genes related to coronary heart disease based on DE analysis and conducted a validation study using real time-qPCR.…”
Section: Methodsmentioning
confidence: 99%
“…Through statistical analyses, Soh et al [ 34 ] identified cancer-related miRNAs associated with somatic copy number alterations and validated them in vitro by measuring the viability and proliferation rates of cells transfected with their inhibitors. Oh et al [ 35 ] identified aging-related genes in the kidney tissue using a regression method and validated them in vivo using mouse and zebrafish models. Joehanes et al [ 36 ] selected genes related to coronary heart disease based on DE analysis and conducted a validation study using real time-qPCR.…”
Section: Methodsmentioning
confidence: 99%
“…Aging-related genes (ARGs) play a vital role in cell senescence and regulate the biological activity of neoplastic tissue [19]. They are associated with many types of cancer, such as renal cell carcinoma and malignant melanoma, and have been shown to hold great promise for clinical application [20,21]. Nonetheless, few studies about BLCA have worked out an effective prognostic model based on ARGs to predict the survival of patients and determine personalized therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Many aging-related cellular events (genomic instability, inflammatory response, immunity, etc.) are hallmarks of cancer ( 9 ). Despite the widespread study of the aging microenvironment in cancers, few studies focused on the overall characteristics of the transcriptional landscape of aging-associated genes in ccRCC.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the widespread study of the aging microenvironment in cancers, few studies focused on the overall characteristics of the transcriptional landscape of aging-associated genes in ccRCC. Previously, several aging-associated genes have been determined to be linked to unfavorable survival outcomes of RCC ( 9 ). Additionally, experimental evidence demonstrates that aging-associated genes participate in RCC progression.…”
Section: Introductionmentioning
confidence: 99%